OPTIMALISASI PELAKSANAAN FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA SALATIGA TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA TAHUN ANGGARAN 2018 DALAM TELAAH UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Wicaksono, Tegar Jati; Madalina, Maria (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
Tegar Jati Wicaksono, E0014396, Optimization Of The Implementation Of The Oversight Function Of The Regional People’s Representative Council Of The City Of Salatiga Against The Regional Budget In 2018 As Part Of The Study Of Law Number 23 Of 2014 Relating To The Regional GovernmentThe purpose of this research is to determine how the supervisory function of the Council of People’s Representation (DPRD) of the Regional Revenue and Expenditure Center (APBD) during fiscal year 2018 is respected in the context of the revision of the Law Number 23 of 2014 concerning the Regional Government. In addition to the supporting and inhibiting factors in the implementation of the DPRD supervision function of the city of Salatiga in the regional budget for the fiscal year 2018. This research is a descriptive empirical legal research. The types of data used are primary data and secondary data. The main sources used are direct interviews with the parties concerned. Secondary data sources include literature, legislation, journals, Internet articles and materials, and other related sources. The data collection technique used is a field study going directly to the subject of research and literature to obtain a theoretical basis for the research. Based on the results of the research and discussions, it was concluded that the implementation of the DPRD oversight function of the City of Salatiga on the regional budget for the 2018 financial year was conducted in accordance with the standards in force, but that its use did not work optimally. In exercising the APBD’s oversight function, the DPRD of Salatiga encountered various obstacles.